Fly ash-based eco-friendly geopolymer concrete: A critical review of the long-term durability properties. (8th February 2021) - Amran, Mugahed; Debbarma, Solomon; Ozbakkaloglu, Togay
Highlights: Significant exposure to fly ash possesses a risk to human health and environment. The large use of fly ash in making GPC can reduce the CO2 emissions and provide cost-benefits. NaOH, KOH, and Na2 SiO3 are most used activator in fly ash-based GPC. Durability of fly ash-based GPC is mainly affected by the fineness of fly ash particles. The long-term durability properties of FA-GPC have a great resistance to aggressive environments. Abstract: Since fly ash (FA) is widely available across the globe, which is used to produce the next generation green concrete for the modern construction. The FA is a pozzolanic material with high alumina and silica content that gives a cementitious property in the presence of water. Thereby, FA-based geopolymer concrete (FA-GPC) seems to be a superlative option over the conventional concrete, to be developed. Using cost-effective and commonly obtainable FA as mineral fillers in concrete brings plentiful advantages to reduce the consumption of ordinary Portland cement (OPC), eliminate the disposal of FA in landfills, and decrease the CO2 emissions, which all contribute toward a clean environment. With FA, a durable FA-GPC is a comparatively new, revolutionary and sustainable engineered composite material with several benefits, including the high early strength and improved durability properties (such as reduced permeability) against aggressive environments. Production of sustainable and greener concretes has become a major interest in the construction industry globally. This paper reviews the clean production, factors affecting the durability of FA-GPC, and the human health and environmental impacts of FA disposal. This review also aims to provide a critical review on the long-term durability properties and the behavior of FA-GPC composites, in addition to synopsize the research development trends to generate comprehensive insights into the potential applications of FA as a sustainable and ecofriendly construction material, for making greener concrete composite, towards industrialize environmentally buildings today.